Persistence of Retinopathy of Prematurity in an Infant with Tetralogy of Fallot - Murat Gunay; Taner Yavuz; Gokhan Celik; Gunay Uludag (Case Reports in Pediatrics)
We report an infant with tetralogy of fallot (TOF) who was born at 35 weeks of gestation and of 1700 g birth weight and presented with persistent retinopathy of prematurity (ROP) at 6 months of age. Follow-up ophthalmic examinations were done at 2, 3, and 4 weeks of age. A demarcation line in Zone II was noticed on the first ocular examination done at 4 weeks of postnatal age. At 6 months of postnatal age, the infant still had an avascular peripheral retina with the demarcation line in Zone II. Even though this index subject did not have any typical risk factors for ROP, TOF seems to be the probable reason for developing as well as persistence of avascular retina.